Bioresources and bioprocess in biotechnology. Volume 1, - Abdulhame, Sabu; Pradeep, N. S.; Sugathan, Shiburaj (Springer, 2017)
This book is a compilation of articles on various aspects of bioresources and the processes employed for its judicious utilization. Biodiversity and conservation, food security, gene banks and repositories, laws governing biodiversity, bioprospecting, bioresources in traditional medicine and biodiversity mining are some of the important topics covered in the book. The unique contents of the book make it an important source of information for conservation scientists, academics, activists and to those who are actively involved in product oriented research from bioresources.
Keywords: Biotechnology.; elektronické knihy; electronic books